Pengelolaan Potensi Bahaya dan Risiko Kerja pada Pekerja Kampung Maggot Bandar Lampung - Berawi, Khairun Nisa; Karima, Nisa; Zahra, Tsurayya Fathma; Siregar, Maulana Irfan Hazairin; Safira, Ditya Ananda; Nurhaliza, Suci; Rahmah, Azizah Nur; Padmadisastra, Jauzaa Faishal Ahmad; Shiddiq, Haikal; Christy, Angelica Philia; Murfi, Syahrani Alya (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Kampoeng Maggot is a subsidiary of Green Gunter Farm which operates in the livestock and fisheries sector which focuses on the BSF (Black Soldier Fly) maggot cultivation sector. The aim of this PKM is to identify potential hazards at Green Gunter Farm and increase workers' understanding of the importance of protective equipment and work compliance by providing interventions to control these potential hazards. The PKM method is carried out by identifying potential hazards and intervention in the form of counseling and creating work SOPs. The identification results show that the greatest risk of work hazards comes from potential ergonomic hazards due to the uneven terrain. Apart from that, workers are also not used to using complete personal protective equipment due to the lack of adequate SOPs. PKM results show an increase in workers' knowledge and attitudes about personal hygiene, PPE, and the work environment, as well as the availability of SOPs that guide safe work flows to minimize potential hazards and work risks.